Heard and Hard Reality of Maternal Health: Are We Oversimplifying the Challenges in Bangladesh? - Afsana, Kaosar (World Scientific, 2022)
This book chapter was published in the book named Voices on South Asia: Interdisciplinary perspectives on Women's Status, Challenges and Futures, and the definite version is available at: https://www.worldscientific.com/doi/abs/10.1142/9789811213267_0015